Investigation and reflection on how the Malaysian based private sector can maximise their contribution towards the implementation of the United Nations Sustainable Development Goals (SDGs) - K.Velautham, Kamalahshunee (2018)
The global community at the United Nations on September 25, 2015 agreed to the 2030 Global Agenda entitled ‘Transforming our world: The 2030 Agenda for sustainable Development’. This action plan which replaces the Millennium Development Goals (MDGs) is universal in nature and comprehensive in the range of issues and concerns addressed pertaining to development, economy, human rights and the environment. The theme of ‘no one will be left behind’ is most critical so as to ensure that inclusive development is within the reach of all people groups and communities.